Cultural diversity and tax compliance of SME entrepreneurs - Yong, SE (Australasian Tax Teachers Association (ATTA), 2012)
Despite the economic importance of the tax collection process undertaken by SMEs, little is known about their tax compliance behaviour, particularly in relation to cultural factors. With the increasing cultural diversity of SMEs in most OECD countries, there is a need to understand how they comply with the tax regulations. This knowledge is important for both tax authorities and the business community, in identifying factors that may hinder successful tax compliance by SMEs. This study aims to examine the tax compliance dynamics of the four largest ethnic SME groups in New Zealand. Additional perspectives were sought from tax practitioners and business experts to provide insights into the cultural influences of networks and time and risk orientations. Collectivistic Maori, Asian, and Pacific groups prefer face-to-face relationship building, so data was gathered by personal interviews with 59 SME entrepreneurs, tax practitioners and business experts, conducted between 2006 and 2010. The study found some collectivistic groups used their networks to lower their tax compliance costs, whereas others were obligated to fulfil their group’s interests, thereby impeding their ability to comply with tax regulation. Ethnic groups with greater reverence towards authorities perceived the tax authority as exerting significant punishment for non-compliance. Finally, ethnic groups that were future oriented experienced fewer tax compliance difficulties. This research showed that some ethnic groups experienced more tax compliance difficulties due to the cultural incompatibility with the New Zealand tax requirements. In order to successfully comply, there is a need for SME entrepreneurs to modify and adapt their cultural values to align with the tax requirements. In addition, tax authorities also need to be culturally aware that some ethnic groups may have compliance difficulties due to their cultural values, thereby requiring targeted monitoring and assistance measures and highlighting that there cannot be “business as usual” for these authorities.
Keywords: Tax compliance; Culture; Diversity